ROLE OF PAP SMEAR TEST: FROM SCREENING TO CURE IN TERTIARY CARE HOSPITAL - Romana Bibi; Hina Niaz; Kainat Sheikh; Maryam Ibrahim (Gandhara University, 2022)
OBJECTIVE This study aims to assess the Pap smear screening method's accuracy in detecting precancerous lesions. METHODOLOGY After fulfilling the inclusion criteria patients were selected, the patient's bladder was emptied and put in a dorsal position, and Cusco's speculum was introduced after lubrication followed by insertion of Ayer's spatula, applied on the transformational zone, and rotated in 360 degrees. Specimen smeared on glass slides and sent to the laboratory with fulfilled lab pre-requisite form. Patients were requested to follow up with a histopathology report. RESULTS Mean age of the patient was 38.111+9.461 years. Among the 77 patients whose samples were taken 15.4% were asymptomatic, 32.1% with vaginal discharge, 17.9% vaginal discharge,17.0% with intermenstrual bleeding and 16.7% were having lower abdominal pain with p-value=0.087. Histopathology reports were interpreted upon follow-up visit among those 1.3% came out to be positive for malignancy, 76.6% negative for malignancy while 22.1% had an inadequate sample. CONCLUSION The most common method for screening for cervical cancer is the Pap smear, but its efficacy in detecting early precancerous lesions is very low, possibly due to laboratory error or false technique to a gynecologist of sample technique in our tertiary care hospital. Other screening methods should be used instead of conventional Pap smear.